Congo 1956-1960 - Paulus, Jean-Pierre; Houphouet-Boigny, Félix (Bruxelles Paris : Terre d'Europe, 1962)
Bibliotheek Camille Huysmans
Dedicator: Paulus, Jean-Pierre, dedicatee: Huysmans, Camille
Frans
Monografie
Keywords: Belgisch Congo